Competency level of extension agents and its relationship on work performance in rice technology transfer at IADA Rompin - Ami Nordin, Huril Ain (2018)
Rice is the staple food of Malaysian and because of this, 12 granary areas have been developed by the government to increase the self-sufficiency level of rice which is now about 73%. There is a huge gap between potential yield and current yield and this issue is also happening in granary areas that are equipped with complete facilities. Rice check manual that has been provided by Department of Agriculture is the basis for rice technology in Malaysia. Extension agents are responsible to transfer this technology to the farmers. This research is to evaluate the competency level of extension agents in rice technology transfer based on the planning, implementing, monitoring activities and work performance. Next is to determine the relationship between the competency level of the extension agents in planning, implementing and monitoring activities and the work performance. Lastly, this research is to identify the strongest independent variables that contribute to work performance. The study is conducted using and analysing 161 established questionnaires that were distributed to farmers in IADA Rompin. Results show that competency level of extension agents in planning, implementing, monitoring activities and work performance is moderate. All independent variables have a positive correlation to the work performance with only monitoring shows high correlation. Next, implementing and monitoring is highly significant with work performance which indicates the strong relationship and contribution to work performance. As a recommendation, IADA Rompin needs to give attention in implementing and monitoring because they are significant with their work performance while improving in planning as it is also important. As a conclusion, implementing and monitoring contribute more to the work performance of extension agents in IADA Rompin.